2018
DOI: 10.1007/s11914-018-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exercise in Rodent Models of Chronic Pain

Abstract: Purpose of ReviewPhysical activity is increasingly recommended for chronic pain. In this review, we briefly survey recent, high-quality meta-analyses on the effects of exercise in human chronic pain populations, followed by a critical discussion of the rodent literature.Recent FindingsMost meta-analytical studies on the effects of exercise in human chronic pain populations describe moderate improvements in various types of chronic pain, despite substantial variability in the outcomes reported in the primary li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 163 publications
2
20
0
1
Order By: Relevance
“…After initiation of the voluntary exercise protocol, the exercise group had a progressive decline in voiding frequency back to the baseline that correlated with an increase in volume per void. Significant differences among groups were seen after 2 weeks of exercise, consistent with prior studies which demonstrated a delay in improved pain outcomes, as measured by tactile allodynia, after 5 days to 6 weeks of exercise . While voiding frequency is clearly not the same as tactile allodynia, these findings support the idea that modulation of either pain or voiding dysfunction is not an immediate response and requires a period of time from the initiation of exercise possibly due to nerve modulation .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…After initiation of the voluntary exercise protocol, the exercise group had a progressive decline in voiding frequency back to the baseline that correlated with an increase in volume per void. Significant differences among groups were seen after 2 weeks of exercise, consistent with prior studies which demonstrated a delay in improved pain outcomes, as measured by tactile allodynia, after 5 days to 6 weeks of exercise . While voiding frequency is clearly not the same as tactile allodynia, these findings support the idea that modulation of either pain or voiding dysfunction is not an immediate response and requires a period of time from the initiation of exercise possibly due to nerve modulation .…”
Section: Discussionsupporting
confidence: 87%
“…While human literature is scant, numerous studies have demonstrated that exercise can either prevent or improve pain and stress metrics, such as autonomic dysfunction and corticosterone levels, in a variety of animal models of chronic pain . Exercise was additionally able to improve bladder function and bladder hypersensitivity in an animal model of chronic stress, however, this study did not evaluate the relationship between the amount of exercise and degree of symptom improvement …”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, the American College of Physicians updated clinical guidelines recommending physical exercise and yoga as the first line therapy for lower back pain (75). While there are many animal studies on exerciseinduced analgesia (76,77), analgesic properties of music have been sparsely investigated in animal models (43) in contrast to growing clinical evidence (22,(24)(25)(26)(78)(79)(80)(81)(82). show that hyperalgesia was observed in animals exposed to control conditions and music-exposed mice show a reduced latency difference.…”
Section: Discussionmentioning
confidence: 99%